Exposure modality, input variability and the categories of perceptual recalibration. (March 2016) - Reinisch, Eva; Mitterer, Holger
Abstract: Recent evidence shows that studies on perceptual recalibration and its generalization can inform us about the presence and nature of prelexical units used for speech perception. Listeners recalibrate perception when hearing an ambiguous auditory stimulus between, for example, /p/ and /t/ in unambiguous lexical context ( kee[p/t] ->/p/, mee[p/t] ->/t/) or visual context (presence vs. absence of lip closure). A later encountered ambiguous auditory-only stimulus is then perceived in line with the previously experienced context. Unlike studies using lexical context to guide learning, experiments with the visual paradigm suggested that prelexical units are rather specific and context-dependent. However, these experiments raised doubts whether lexically-guided and visually-guided recalibration are targeting the same type of units, or whether learning in the visually-guided paradigm—with limited variability during exposure—is task-specific. The present study shows successful visually-guided learning following exposure to a variety of different learning trials. We also show that patterns of generalization found with the visually-guided paradigm can be replicated with a lexically-guided paradigm: listeners do not generalize a recalibrated stop contrast across manner of articulation. This supports suggestions that the units of perception depend on the distribution of relevant cues in the speech signal. Highlights: Recalibration of speech perception for place of articulation contrasts is robust. Visually-guided recalibration is found with high-variability exposure. A recalibrated place contrast is not generalized across manner of articulation. Speech perception may make use of context-dependent sub-lexical units.